Majoru pamatskolas atbalsta komandas sociālpedagoģiskā darbība 9. klašu skolēnu no sociālā riska ģimenēm tālākās izglītības veicināšanā - Bērziņa, Līga (Latvijas Universitāte, 2009)
Diplomdarbā risina aktuālu problēmu par 9.klašu skolēnu no sociālā riska ģimenēm nākotnes plāniem pēc pamatizglītības iegūšanas. Tika veikts pētījums par 2007./08.māc.g. un 2008./09.māc.g. 8. – 9.klašu skolēnu no sociālā riska ģimenēm nākotnes plāniem pēc pamatskolas absolvēšanas. Rezultāti parādīja, ka vairāki skolēni vēl nav izvēlējušies savu nākotnes profesiju, bet tie, kuri ir izvēlējušies, nezina, kur to var apgūt un kādam ir jābūt sekmju līmenim, lai varētu iestāties attiecīgajā izglītības iestādē. Autores izveidotā programma radīja iespēju Majoru pamatskolā izveidot atbalsta komandu, kuras locekļi savas kompetences robežās spētu veicināt 9.klašu skolēnu tālākās izglītības izvēli. Atslēgas vārdi: atbalsta komanda, komanda, sociālā riska ģimene, sociālpedagoģiskā darbība, tālākizglītība.

The Diploma Paper deals with the topical problems concerning the future plans after graduating from the lower secondary school of the pupils from the Grade 9 coming from the social risk families. The case study was carried out with regard to the future plans after graduating from the lower secondary school of the pupils coming from the social risk families studying in the Grades 8 and 9, academic years 2007/ 2008 and 2008/2009. The data gathered proved that there are several pupils that have not yet chosen their future profession. However, those who have chosen the profession do not know where they can study to acquire the desired profession or have no idea of the level of knowledge necessary to enter the desired educational institution. The programme developed by the author of the Diploma Paper gave the possibility to make a support team in Majori Primary School promoting the choice of the future education of the Grade-9-pupils. Key words: continuing education, social risk family, socio-pedagogical activities, support team, team.
Socio-pedagogical activities of the support team in Majori primary school in promoting the continuation of education of Grade 9 pupils coming from social risk families
Keywords: Pedagoģija